PHENOTYPIC DETECTION OF ESBL AND AMPC BETA LACTAMASES AMONG GRAM-NEGATIVE ISOLATES FROM CLINICAL SAMPLES IN A TERTIARY CARE HOSPITAL - BHAVANA, DASARI; MUSADDIQ, SHABNUM; K, SAILEELA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Drug-resistant Gram-negative bacilli expressing extended-spectrum beta-lactamases (ESBLs) and AmpC pose a serious therapeutic threat in nosocomial infections. Cost-effective screening methods are a boon to patients. This study aims to detect gram-negative bacilli and their antibiotic sensitivity patterns, as well as detect the ESBL and AmpC-producing isolates among Gram-negative bacilli. Methods: A prospective study was conducted with 150 samples. Gram-negative bacilli were isolated, and their antibiotic sensitivity tests were performed by the Kirby–Bauer disk diffusion method. Potential ESBL producers were screened using Ceftazidime disc, and AmpC producers were screened by Cefoxitin discs by the disc diffusion method. ESBL producers were confirmed by the combined disc diffusion assay method using ceftazidime and ceftazidime/Clavulanic acid disc. AmpC producers were confirmed by the Cefoxitin Cloxacillin Double Disc Synergy Test. Results: About 38% of 150 samples were gram-negative bacilli, of which 40.35% were Escherichia coli, followed by Pseudomonas aeruginosa (35.08%). Maximum sensitivity by E. coli was found toward imipenem, meropenem, and cotrimoxazole. P. aeruginosa showed maximum sensitivity toward piperacillin/tazobactam, imipenem, meropenem, and ceftazidime. 28.07% of Gram-negative isolates were ESBL producers, with E. coli (11 isolates) being the maximum, and 15.78% were AmpC producers, with E. coli (four isolates) being the maximum. Seven isolates were both ESBL and AmpC producers. Conclusion: Routine screening and timely reporting of ESBL and AmpC producers help in preventing the spread of multidrug-resistant strains. Antibiotic resistance surveillance helps in the implementation of strict infection control and prevention practices.